2009
DOI: 10.1111/j.1540-8167.2009.01579.x
|View full text |Cite
|
Sign up to set email alerts
|

Slow Wall Motion Rather Than Electrical Conduction Delay Underlies Mechanical Dyssynchrony in Postinfarction Patients With Narrow QRS Complex

Abstract: Dyssynchronous segments of an ischemic myocardium show unimpaired local activation but slow wall motion, thereby limiting the benefit of ventricular preexcitation via CRT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 31 publications
0
10
1
Order By: Relevance
“…Regional contractility and conduction velocity were lowest in MI segments and intermediate in peri-MI segments, unlike the study by Klemm et al [30] in patients with ischemic cardiomyopathy, which found viability and increased CV in areas with slow wall motion. We did not find mechanical delays in the peri-MI zones despite reduced regional function at 1 week post MI.…”
Section: Discussioncontrasting
confidence: 86%
“…Regional contractility and conduction velocity were lowest in MI segments and intermediate in peri-MI segments, unlike the study by Klemm et al [30] in patients with ischemic cardiomyopathy, which found viability and increased CV in areas with slow wall motion. We did not find mechanical delays in the peri-MI zones despite reduced regional function at 1 week post MI.…”
Section: Discussioncontrasting
confidence: 86%
“…Therefore, an meta-analysis of individual data from patients treated with intramyocardial stem cell therapy has started and will be completed by the end of 2011. 98 Most NOGA ® -guided therapeutic studies targeted the injections either to the border zone of infarction (identi fied by decreased unipolar voltage and moderately decreased LLS), or areas of chronic ischemia (identified by normal or decreased unipolar voltage and moderately to severely decreased LLS). The site of the intramyocardial injections is selected mainly on the basis of the NOGA ® unipolar voltage and LLS maps, relying on their diagnostic and prognostic values and their excellent correlation with ischemia-related images obtained with noninvasive techniques.…”
Section: Functional Recovery After Pcimentioning
confidence: 99%
“…The larger EMD is a result of the increased force required to generate shortening within the late activated region [15]. Interestingly, there can even be a mechanical delay without any evidence of electrical activation delay [17]. Most of these studies, however, have been conducted in canine models of LBBB and it is uncertain how this relationship manifests in patients undergoing CRT.…”
Section: Introductionmentioning
confidence: 99%